The strongest predictors of compliance with health protocols among marketers and guilds based on the transtheoretical model - Shandiz Moslehi; Asghar Tavan; Sajjad Narimani; Fardin shahbazzadeh; Nadia Sedri; Sama Sabahi (BMC, 2024)
Abstract Background Global communication, an integral part of modern life, increases the risk of transmitting infectious diseases to individuals. Based on the transtheoretical model (TTM), this study aimed to identify the most effective factors in adherence to health protocols among marketers and guilds. Methods This cross-sectional study was conducted among 400 market sellers and guilds of Ardabil City, Iran, in 2023. The TTM questionnaire was distributed among the participants which included four sub-constructs: (1) stages of change, (2) process of change, (3) self-efficacy, and (4) decisional balance. The data were analyzed using SPSS version 20. One-way ANOVA and linear regression tests were employed to evaluate the prediction of effective factors of the stage transition. Results Most participants (63.5%) were between 21 and 40. Most participants (65.5%) were in the passive stages of change (precontemplation, contemplation, and preparation). Pros (β = 0.133, P < 0.001) and behavioral processes of change (β = 0.058, P < 0.001) were the strongest predictors of the stage of change or improvement of stages of participants' willingness to follow health protocols. Conclusion A correct understanding of the stages of behavior change can strengthen strategies for promoting healthy behaviors. Also, understanding the benefits of healthy behavior means compliance with health protocols and behavioral processes such as stimulus control, reinforcement management, counterconditioning, and self-liberation, along with high self-efficacy, have an impact on improving the stages of behavior change.